Activated γδ T cells inhibit osteoclast differentiation and resorptive activity in vitro. (6th October 2013) - Pappalardo, A.; Thompson, K.
Summary Extensive evidence suggests that the immune system exerts powerful effects on bone cells, particularly in chronic disease pathologies such as rheumatoid arthritis (RA). The chronic inflammatory state in RA, particularly the excessive production of T cell‐derived proinflammatory cytokines such as tumour necrosis factor (TNF)‐α and interleukin (IL)‐17, triggers bone erosions through the increased stimulation of osteoclast formation and activity. While evidence supports a role for IL‐17 and TNF‐α secreted by conventional CD4+ T cells in RA, recent evidence in animal models of RA have implicated γδ T cells as a major producer of pathogenic IL‐17. However, the capacity of γδ T cells to influence osteoclast formation and activity in humans has not yet been investigated widely. To address this issue we investigated the effects of γδ T cells on osteoclast differentiation and resorptive activity. We have demonstrated that anti‐CD3/CD28‐stimulated γδ T cells or CD4+ T cells inhibit human osteoclast formation and resorptive activity in vitro. Furthermore, we assessed cytokine production by CD3/CD28‐stimulated γδ T cells and observed a lack of IL‐17 production, with activated γδ T cells producing abundant interferon (IFN)‐γ. The neutralization of IFN‐γ markedly restored the formation of osteoclasts from precursor cells and the resorptive activity of mature osteoclasts, suggesting that IFN‐γ is the major factor responsible for the inhibitory role of activated γδ T cells on osteoclastogenesis and resorptive activity of mature osteoclasts. Our work therefore provides new insights on the interactions between γδ T cells and osteoclasts in humans.